Beverly Hills cop III - Rodgers, Nile.; Bach, Danilo; Petrie, Daniel, Jr.; Landis, John, 1950-; Neufeld, Mace.; Rehme, Robert, 1935-; De Souza, Steve; Murphy, Eddie, 1961-; Reinhold, Judge, 1957-; Elizondo, Hector; Randle, Theresa, 1967-; Eddie Murphy Productions (Firm); et al. (Hollywood, Calif. : Paramount, 2001)
Detroit cop Axel Foley returns and is in pursuit of the bad guys at LA's popular theme park, WonderWorld.
Originally produced as a motion picture in 1994.
Special features: new exclusive cast and crew interviews, theatrical trailer.
Music score by Nile Rodgers ; based on characters created by Danilo Bach and Daniel Petrie, Jr.
Eddie Murphy, Judge Reinhold, Hector Elizondo, Theresa Randle.
MPAA rating: Rated R, for language and some violence ; CHV rating: 14A.
DVD ; widescreen version (16:9) ; Dolby digital 5.1 surround, Dolby surround or stereo ; NTSC, region 1.
Keywords: Foley, Axel (Fictitious character) -- Drama; Counterfeits and counterfeiting -- Drama; Automobile theft investigation -- Drama; Police, Black -- Drama; Detective and mystery plays; Murder -- Investigation -- Drama; Closed caption video recordings; Detroit (Mich.) -- Drama; Los Angeles (Calif.) -- Drama; California -- Los Angeles; Michigan -- Detroit; Film sequels; French language materials -- Bilingual; DVD-Video discs; Film sequels; Drama; Feature films; Comedy films